Implementation of the Youth Guarantee Programme in Romania - Petrescu, Claudia; Neguț, Adriana; Mihalache, Flavius (Calitatea Vieții, 2021)
In 2014, European countries began implementing the Youth Guarantee Programme (YGP), one of the European Commission’s most important initiatives designed to combat the issue of youth unemployment. This led to a decrease in the number of young NEETs over the subsequent 6 years. Based on data concerning the extent and size of the NEETs phenomenon at the European level, the number of NEETs who benefit from various measures, and data regarding programmes for NEETs financed by ESF, this paper presents an overview of the YGP implementation in Romania during the 2014−2020 period. It does so by identifying the main challenges and barriers that prevented the achievement of the proposed results. In that regard, the main barriers in the implementation of YGP in Romania are related to the lack of coordination of measures between institutions; a lack of flexibility in registering young NEETs; low levels of partnership with local authorities, companies, and NGOs; delays in funding measures; and a lack of centralised monitoring data in order to provide a picture of progress and thus necessary improvement measures.